A Curtural Approach To Tourism Through The Technopreneur Model - Tunul Lasniatin; Budi Ilham Maliki; Dekha Aliya Nul’ulum (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2024)
One way to develop tourism in Banten to achieve these contributions is through a cultural approach using the technopreneur model. This approach is interesting to study and apply in tourism development because its concept integrates and collaborates the strengths of cultural roles, technological roles, and entrepreneurial spirit. This integration allows for mutual development among culture, technology, entrepreneurship, and tourism to achieve the aforementioned goals. This study aims to describe the cultural approach in tourism development, and the application of the cultural approach in Banten tourism development through the technopreneur model. To achieve these objectives, a qualitative research method was used with a literature review approach. Data is obtained by reading theories that are relevant to the research problems. The study was conducted in January-June 2024. Data credibility is carried out by increasing the number of journals used as references. Data analysis is carried out using four stages, starting from data collection, data classification, data reduction, and drawing conclusions. The results of the literature review study concluded that the cultural approach model for Banten tourism can be concluded through the following steps. First, Banten tourism must be developed by paying attention to, maintaining, preserving, developing, advancing, and utilizing the diversity. Second, creating and growing entrepreneurs who have an entrepreneurial spirit. Third, through the technopreneur model, steps are taken to pay attention to, maintain, preserve, develop, advance, and utilize the diversity. Fourth, working on diverse cultural tourism so that it attracts many tourists to visit; creating and growing tourism entrepreneurs. Fifth, optimizing the cultural approach with the integration of technological competence and entrepreneurial spirit in tourism development. Sixth, the maintenance, preservation and development of the main characteristics of Banten.Keywords: Cultural approach, tourism, technopreneur model.